La reutilització de les fonts en el «Tirant lo Blanch» - Alemany i Ferrer, Rafael (Caplletra. Revista Internacional de Filologia, 1997)
When analysing Martorell' s novel we find a recurrent feature suclt as the re-utilisation of differentliterary sourees. This re-utilisations may prevent the reader from grasping the key points of Tirant lo Blanch. From this point of view Rafael Alemany analyses the Valencian author's modus operandi when reusing texts such as Llibre d'ordre de cavalleria, Lancelot en prosa or Voyage d'outre mer and the new spirit present in Tirant. On the other hand, the study of the sources of this Valencian work can enable us to confirm the hypothesis that Tirant lo Blanch was written only by one author.